Effect of Sexual Counseling Training in Gynecological Cancers According to the PLISSIT Model on Midwifery Students' Awareness and Attitude: A Randomized Clinical Trial - Ahsen DEMİRHAN KAYACİK; Yasemin HAMLACI BAŞKAYA; Kevser İLÇİOĞLU (Shiraz University of Medical Sciences, 2024)
Background: It is very important to show health professionals and students that sexuality is important in women with gynecological cancer, to increase their awareness in this area and to ensure the formation of positive attitudes towards sexuality. This study aimed to determine the effect of sexual counseling training in gynecological cancers according to the PLISSIT Model on Midwifery students' Awareness and Attitude.Methods: This randomized controlled study was conducted between May and November 2022 by midwifery students studying at Sakarya University in Turkey. 36 students were allocated to the control group and 38 to the intervention group using block randomization. The intervention group was given 3 sessions training based on the PLISSIT model, whilethe control group underwent no training. Data were collected before the training and one month after completing the intervention using the Gynecological Cancer Awareness Scale (GCAS) and Sexual Attitudes and Beliefs Scale (SABS). Data analysis was done using SPSS software version 22 with Chi square test, independent and paired t-test. A significance level of P<0.05 was used.Results: In the intervention group, a significant difference was found within the group in terms of the GCAS (P<0.001), and SABS (P<0.001) scores after the study. In the control group, there was no significant difference within the group in terms of the GCAS (P=0.16) and SABS (P=0.26) scores. There was a significant difference between the intervention and control groups in terms of GCAS (P=0.004) and SABS (P<0.001) scores one month after training.Conclusion: It was found that sexual counseling training in gynecological cancers according to the PLISSIT Model was effective in creating awareness and positive attitudes in mMidwifery students.Trial Registration Number: NCT05967104.